Role of plant defense in the utilization of native browse in southern Ethiopia - Woodward, A.; Coppock, D. Layne (Springer, 1995)
Browse is an important forage in pastoral systems, especially during dry seasons, because it is high in nitrogen and digestibility. However, browse palatability may be reduced by possible plant defenses such as tannins and physical attributes. Chemical and physical properties of 20 browse species were correlated with the feeding preference of camels, sheep and goats during wet and dry seasons in a densely wooded, semi-arid savanna. Preference was assessed by comparing relative use with abundance of browse species. Chemical components included nitrogen, available nitrogen, acid-detergent fibre, in vitro digestibility, total tannins, and condensed tannins. Physical defenses included thorns, hooks, spines, and leaf surface properties. Animal preference was negatively related to chemical and physical defense factors, positively related to N content, and unrelated to fibre and digestibility with results depending on animal species and season. Understanding the physical and chemical factors which influence browse selectivity aids in identifying promising forage resources.